Differentiation of ICOS+ and ICOS− recent thymic emigrant regulatory T cells (RTE Tregs) during normal pregnancy, pre‐eclampsia and HELLP syndrome. (12th October 2015) - Wagner, M. I.; Jöst, M.; Spratte, J.; Schaier, M.; Mahnke, K.; Meuer, S.; Zeier, M.; Steinborn, A.
Summary: Two different subsets of naturally occurring regulatory T cells (nTregs ), defined by their expression of the inducible co‐stimulatory (ICOS) molecule, are produced by the human thymus. To examine the differentiation of ICOS + and ICOS − CD45RA + CD31 + recent thymic emigrant (RTE) Tregs during normal pregnancy and in the presence of pre‐eclampsia or haemolysis elevated liver enzymes low platelet (HELLP)‐syndrome, we used six‐colour flow cytometric analysis to determine the changes in the composition of the ICOS + and ICOS − Treg pools with CD45RA + CD31 + RTE Tregs, CD45RA + CD31 − mature naive (MN) Tregs, CD45RA − CD31 + and CD45RA − CD31 − memory Tregs . With the beginning of pregnancy until term, we observed a strong differentiation of both ICOS + and ICOS − CD45RA + CD31 + RTE, but not CD45RA + CD31 − MN Tregs, into CD45RA − CD31 − memory Tregs . At the end of pregnancy, the onset of spontaneous term labour was associated with a significant breakdown of ICOS + CD45RA − CD31 − memory Tregs . However, in the presence of pre‐eclampsia, there was a significantly increased differentiation of ICOS + and ICOS − CD45RA + CD31 + RTE Tregs into CD45RA − CD31 + memory Tregs, wherein the lacking differentiation into CD45RA − CD31 − memory Tregs was partially replaced by the increased differentiation of ICOS + and ICOS − CD45RA + CD31 − MN Tregs into CD45RA − CD31 − memory Tregs . In patients with HELLP syndrome, this alternatively increased differentiation of CD45RA − CD31 − MN Tregs seemed to be exaggerated, and presumably restored the suppressive activity of magnetically isolated ICOS + and ICOS − Tregs, which were shown to be significantly less suppressive in pre‐eclampsia patients, but not in HELLP syndrome patients. Hence, our findings propose that the regular differentiation of both ICOS + and ICOS − CD45RA + CD31 + RTE Tregs ensures a healthy pregnancy course, while their disturbed differentiation is associated with the occurrence of pre‐eclampsia and HELLP syndrome.